Weighted sticker system - Gan, Yee Siang; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2012)
A sticker system is a computational model which uses a sticker operation on DNA molecules. A sticker operation works on the complementary relation of double stranded DNA by using ligation and annealing operation to form a complete double stranded DNA sequence. In this paper, a new variant of sticker systems, called weighted sticker systems, is introduced. Some basic properties of language families that are generated by the weighted sticker systems are investigated.This paper also introduces some restricted weighted variants of sticker systems such as weighted one-sided, regular, simple, simple one-sided and simple regular sticker systems. Moreover, the paper shows that the presence of weights increases the generative powers of usual variants of sticker systems.